Public morality as an object of national security of Ukraine: theoretical and legal aspect - Горєлова, Вероніка Юріївна; Горєлова, В. Ю.; Horielova, Veronika Yu.; Horielova, V. Yu. (Одеса : Гельветика, 2020)
У статті досліджується питання про доцільність впровадження духовних і морально-етичних цінностей як об’єкта захисту службою національної безпеки України відповідно до внесеного до Верховної Ради України проєкту Закону про внесення змін до Закону України «Про Службу безпеки України» щодо вдосконалення організаційно-правових засад діяльності Служби безпеки України. Встановлено, що як об’єкт національної безпеки суспільна мораль може трактуватися у вузькому й широкому значенні. У широкому значенні такий об’єкт суспільної моралі можна трактувати як систему державних цінностей, таких як суверенітет, мова, територіальна цілісність, здоров’я, честь, гідність, недоторканність особи тощо. У вузькому значенні об’єктом суспільно моралі виступає духовний стан кожної окремої людини, адже людина відповідно до Основного закону України є найвищою цінністю. Зрозуміло, що суспільну мораль не можливо «запрограмувати» навіть трактуванням практики минулого всесвітнього досвіду, й, таким чином, моральні цінності доречніше закласти в правове поле, що підлягає охороні. На наш погляд, суспільна мораль як об’єкт охорони Службою безпеки України повинна якраз містити у своїй структурі цінності й уявлення, пов’язані із життям суспільства, а також відповідні цим цінностям вимоги й практики. Чинне законодавство України, яке покликане забезпечити захист прав і свобод людини, на жаль, не містить тлумачення поняття «мораль» й «суспільна мораль». Не дивлячись на те, що кожна людина здатна розуміти добро й зло, корисне й шкідливе, вона також підкорена власним уявленням про добре й погане. У рамках закону створюється базовий обсяг обов’язків, стандарт моральної поведінки, необхідний для нормального функціонування всього суспільства. Таким чином, закон хоча й не може виражати волю кожного й не може відповідати моральним уявленням про справедливість кожного, однак саме в демократичних, правових державах завдяки закону утворюється особистий простір людини, в якому вона гармонійно уживається зі своїми власними міркуваннями про мораль. Мораль як специфічний об’єкт служби національної безпеки України повинна утворювати своєрідний кодекс належного й позитивного досвіду для суспільства, регулювати поведінку, мати особливий духовний вимір і виконувати в суспільстві цілий ряд соціально-значущих функцій, які будуть сприяти гармонізації особи й суспільства.

The article examines the expediency of introducing spiritual and moral and ethical values as an object of protection by the National Security Service of Ukraine in accordance with the draft Law on Amendments to the Law of Ukraine “On the Security Service of Ukraine” to improve organizational and legal principles. activities of the Security Service of Ukraine. It is established that as an object of national security, public morality can be interpreted in a narrow and broad sense. In a broad sense, such an object of public morality can be interpreted as a system of state values, such as sovereignty, language, territorial integrity, health, honour, dignity, inviolability of the person and so on. In the narrow sense, the object of social morality is the spiritual state of each individual, because a person according to the Basic Law of Ukraine is the highest value. It is clear that public morality cannot be “programmed” even by interpreting the practice of past world experience, and thus moral values are more appropriate to lay in the legal field to be protected. In our opinion, public morality as an object of protection by the security service of Ukraine should include in its structure values and ideas related to the life of society, as well as requirements and practices corresponding to these values. The current legislation of Ukraine, which is designed to protect human rights and freedoms, unfortunately, does not contain an interpretation of the concept of “morality” and “public morality”. Even though everyone can understand good and evil, useful and harmful, he is also subject to his own ideas of good and bad. Under the law, a basic amount of responsibilities is created, the standard of moral behaviour necessary for the proper functioning of society. Thus, although the law cannot express the will of everyone and cannot correspond to the moral idea of justice of everyone, it is in democratic, legal states that the law creates a personal space of man, in which he harmoniously coexists with his own considerations of morality. Morality as a specific object of the national security service of Ukraine should form a kind of code of appropriate and positive for society, regulate behaviour, have a special spiritual dimension and perform in society several socially significant functions that will promote harmonization of person and society. Although the law cannot express the will of everyone and cannot correspond to the moral notion of justice of everyone, it is in democratic, legal states that the law creates a person’s personal space in which he harmoniously coexists with his own considerations of morality. Morality as a specific object of the national security service of Ukraine should form a kind of code of appropriate and positive for society, regulate behaviour, have a special spiritual dimension and perform in society a number of socially significant functions that will promote harmonization of person and society. Although the law cannot express the will of everyone and cannot correspond to the moral notion of justice of everyone, it is in democratic, legal states that the law creates a person’s personal space in which he harmoniously coexists with his own considerations of morality. Morality as a specific object of the national security service of Ukraine should form a kind of code of appropriate and positive for society, regulate behaviour, have a special spiritual dimension and perform in society a number of socially significant functions that will promote harmonization of person and society.
Горєлова В. Ю. Public morality as an object of national security of Ukraine: theoretical and legal aspect / В. Ю. Горєлова // Юридичний вісник. - Одеса : Гельветика - 2020. - № 5. - С. 98-104.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; суспільна мораль; об’єкт національної безпеки; людські цінності; принципи; public morality; object of national security; human values; principles